Simplify Boolean algebra

f(X,Y,Z)=(X’Y+XZ)(X+Y’)

1 answer

Use the distributive properties:

(X’Y+XZ)(X+Y’)
=X(X’Y+XZ) + Y’(X’Y+XZ)
=(XX'Y + XXZ) + (X'YY' + XY'Z)
=(Y+XZ) + (X'+XY'Z) [XX'=YY'true, XX=X]
=Y + X' + XZ + XZY'
=Y + X' + XZ [XZ+XZY' = XZ (absorption)]

Now your turn to do some work:
check the above simplification using a truth table on the original expression, and the simplified version.
Similar Questions
  1. Simplify the following functions using Boolean algebra:Y_1=ABC + AB'C'+AB'C. Y_2=A'BC' + AB'C + AB'C'.
    1. answers icon 1 answer
  2. Simplify this function using Boolean algebra laws?I am stuck on this part of my homework (x2'x1'x0') + (x2'x1x0) + (x2x1x0') I
    1. answers icon 1 answer
  3. Boolean algebra is: (1 point)algebra using hexadecimal numbers. a collection of transistors. the branch of math that deals with
    1. answers icon 1 answer
  4. Simplify:(x * y) + (~x * z) + (y * z) I'm using ~ to represent NOT, * to represent AND, + to represent OR I did: (x * y) + (~x *
    1. answers icon 3 answers
more similar questions